Fishermen's Adaptation Due to Global Climate Change - Ernawati S. K (Universitas Negeri Makassar, 2023)
World climate change is a real phenomenon that occurs today. The impact of climate change is certainly significant enough to affect all human life so the purpose of this article is to describe fishermen's adaptation to climate change and the strategies needed as conceptual solutions to current problems, especially in traditional fishermen. This article uses a literature study method where the data obtained are compiled, analyzed, then draw conclusions. Data type, is secondary data. Data collection techniques through stages are data from libraries. Then it is read, recorded, then processed. The results of the study show that fishermen's adaptation strategies in facing famine due to climate change can be done through several strategies, such as adaptive behavior, adaptive Stretegies, and adaptive processes. For this reason, the ability of all family members is needed to manage the various assets they have for their survival, by managing labor assets and human capital assets, such as involving wives and children and utilizing the status or capacity of other family members according to their skills and education. However, for traditional fishing families with low socioeconomic level conditions, in order to sustain to meet the needs of their families, a coping strategy is needed, namely, by increasing income through the use of other resources or reducing expenditure through reducing the quantity and quality of goods or services. In addition, it can also use a family livelihood strategy by applying a dual income pattern which is part of the economic strategy.